Images, Civic Identity, and Cultural Narratives of Puerto Rico: Using Intertextual Articulation to Develop Culturally Responsive Practices. (3rd April 2019) - Berson, Ilene R.; Berson, Michael J.; López de Méndez, Annette
Abstract : Through a collaboration between a university in the US Southeast and a university in Puerto Rico, the researchers explored the use of primary sources to challenge mainstream assumptions and views of Puerto Rico and support application of content and pedagogic approaches into early childhood and elementary classrooms among preservice teachers working in schools in a region with a growing Puerto Rican population. The researchers investigated how preservice teachers' potential for culturally responsive teaching influenced their selection and application of primary sources, cultural narratives, and intertextual articulation as tools to counter narratives of colonialism and oppression that suppress the civic identity formation of young children. The findings suggest that preservice teachers with high potential for culturally responsive pedagogy have greater success integrating inquiry-based learning experiences to support children in challenging historical metanarratives as they synthesize information across intertextual resources. Through the act of interpretation and interrogating multiple viewpoints, children may reclaim their civic identities as they reconsider all the possibilities of meaning encapsulated by a snapshot in time.